2021
DOI: 10.1007/s10571-021-01062-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Serum Removal on Gene Expression and Morphological Plasticity Markers in Differentiated SH-SY5Y Cells

Abstract: Despite the widespread use of the SH-SY5Y human neuroblastoma cell line in modeling human neurons in vitro, protocols for growth, differentiation and experimentation differ considerably across the literature. Many studies fully differentiate SH-SY5Y cells before experimentation, to investigate plasticity measures in a mature, human neuronal-like cell model. Prior to experimentation, serum is often removed from cell culture media, to arrest the cell growth cycle and synchronize cells. However, the exact effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…PRKCA) in BRT-differentiated SH-SY5Y cells compared to undifferentiated cells, as reported previously for RA-, RA/BDNF- or RA/TPA-differentiated cells 49,71,74 . Finally, we found that both BMP4 pre-treatment and the removal of serum during the RA and/or TPA led to a more pronounced increase in neurite length, as described previously for serum removal 75 , and more pronounced changes in the levels of lipid species associated with SH-SY5Y cells differentiation.…”
Section: Discussionsupporting
confidence: 84%
“…PRKCA) in BRT-differentiated SH-SY5Y cells compared to undifferentiated cells, as reported previously for RA-, RA/BDNF- or RA/TPA-differentiated cells 49,71,74 . Finally, we found that both BMP4 pre-treatment and the removal of serum during the RA and/or TPA led to a more pronounced increase in neurite length, as described previously for serum removal 75 , and more pronounced changes in the levels of lipid species associated with SH-SY5Y cells differentiation.…”
Section: Discussionsupporting
confidence: 84%
“…A number of studies have differentiated the SH-SY5Y cell line with RA for a short duration of 2–4 days, at which point the cells are then treated with a chemical factor, to evaluate the inhibitory or stimulatory effect on neurite outgrowth over a specified period 13 , 29 , 30 . However, such short differentiation protocols would be insufficient to produce a population of terminally differentiated cells 31 . Hence, their use is unlikely to capture the behaviour of mature neurons 28 .…”
Section: Resultsmentioning
confidence: 99%
“… 12 Moreover in presence of C2C12 conditioned media, we observed a progressive centrifugal migration of the spinal cord cells, possibly in the attempt to arrange in a monolayer in search to a better access to nutrients present in the C2C12-medium, compared to the multilayer disposition in the slice. Lastly, we cannot exclude that the presence of FBS in the culture medium could partially affect the morphological changes we observed 37 as well as its eventual deprivation: 38 however, the significant differences between the treated and untreated samples confirm the prevailing and effective action of the conditioned media.…”
Section: Discussionmentioning
confidence: 73%